2015
DOI: 10.1088/0953-8984/27/22/226003
|View full text |Cite
|
Sign up to set email alerts
|

Spin-driven symmetry breaking in the frustratedfccpyrite MnS2

Abstract: We report the characterisation of natural samples of the cubic pyrite mineral MnS2 using very high resolution synchrotron X-ray diffraction techniques. At low temperatures we find a new low temperature polymorph, which results from coupling between magnetic and lattice degrees of freedom. Below the magnetic ordering temperature TN = 48 K, we detect a pseudo-tetragonal distortion with a tiny c/a ratio of 1.0006. The structure can be refined in the space group P bca The symmetry lowering reduces magnetic frustra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…The same study also found two branches of spin-wave excitations: a nearly flat one at about 2 meV and a strongly dispersing one (2-7 meV) with a spin gap of 2 meV that is unusually large for the Mn 2+ ion in the spin- 5 2 state [29]. Very recently, the lock-in transition to the commensurate AFM phase received a natural explanation as a result of a tiny tetragonal distortion of the lattice with the c/a ratio of 1.0006 that could be resolved in a synchrotron x-ray diffraction (XRD) experiment [31]. This distortion is sufficient to lift the geometric frustration on the face-centred cubic (fcc) magnetic sublattice of Mn 2+ ions and stabilize long-range AFM order.…”
Section: Historical Perspectivementioning
confidence: 99%
“…The same study also found two branches of spin-wave excitations: a nearly flat one at about 2 meV and a strongly dispersing one (2-7 meV) with a spin gap of 2 meV that is unusually large for the Mn 2+ ion in the spin- 5 2 state [29]. Very recently, the lock-in transition to the commensurate AFM phase received a natural explanation as a result of a tiny tetragonal distortion of the lattice with the c/a ratio of 1.0006 that could be resolved in a synchrotron x-ray diffraction (XRD) experiment [31]. This distortion is sufficient to lift the geometric frustration on the face-centred cubic (fcc) magnetic sublattice of Mn 2+ ions and stabilize long-range AFM order.…”
Section: Historical Perspectivementioning
confidence: 99%
“…[14][15][16] By using very high resolution synchrotron x-ray diffraction techniques, a pseudo-tetragonal distortion was detected below the magnetic ordering temperature (c/a ratio 1.0006), indicating coupling between magnetic and lattice degrees of freedom. 17 Giant pressure-induced volume collapse accompanied by high spin (S = 5/2) to low spin (S = 1/2) transition involving interplay between crystal field splitting and Hund's rule coupling has been observed in this pyrite mineral. 18 The measured Néel temperature of MnTe 2 has been found to show unusually large pressure dependence of 12K/GPa, giving rise to large violation of Bloch's rule.…”
Section: Af Orders On the Fcc Latticementioning
confidence: 78%
“…We used the same well-characterised natural sample of MnS 2 as employed in our previous investigations [9][10][11]16 . This was finely ground and loaded into diamond anvil cells for Raman and x-ray investigations.…”
Section: Methodsmentioning
confidence: 99%
“…For example, huge hysteresis was discovered in MnS 2 , and the thermodynamic boundaries between the pyrite and arsenopyrite phases are unknown. Furthermore, decomposition 15 to MnS + S is found at ambient pressure and only 530 K. Meanwhile, at much lower temperatures, yet another polymorph is found 16 around the magnetic ordering temperature of 48 K. The ordering temperature has been shown to sharply rise under pressure 17 , however its possible intersection with the arsenopyrite polymorph is unknown. The vibrational and electronic properties of the high pressure phase are also unknown, although DFT calculations were originally used to speculate that it would be insulating.…”
Section: Introductionmentioning
confidence: 99%